Faunistic, ecological, and zoogeographical survey of heterobranch fauna in the Adriatic Sea: experiences from Slovenia - LIPEJ, LOVRENC; FORTIČ, ANA; TRKOV, DOMEN; MAVRIČ, BORUT; IVAJNŠIČ, DANIJEL (Mediterranean Marine Science, 2025)
The heterobranch fauna recorded to date in the Slovenian part of the Adriatic Sea was reviewed and analysed in order to present an updated inventory. The ecological traits and zoogeographical affiliation of the recorded heterobranchs were also analysed. The new data revealed that the heterobranch fauna in the area consists of at least 157 species with the majority being nudibranchs (61.4%). The bulk of heterobranchs were considered as Atlanto-Mediterraneans. Heterobranch diversity was found to be significantly related to the number of sampling events. The spatial pattern of heterobranch species and their composition structure in parts of the study area were linked to specific human-impacted areas (HIAs) such as coastal wetlands, ports, and mariculture facilities. Better examination of less investigated environments, new sampling techniques, and citizen science involvement will doubtlessly increase the numbers in this checklist.